2021
DOI: 10.1037/apl0000929
|View full text |Cite
|
Sign up to set email alerts
|

Making daily decisions to work from home or to work in the office: The impacts of daily work- and COVID-related stressors on next-day work location.

Abstract: To protect workers' safety while gradually resuming on-site operations amid the COVID-19 pandemic, many organizations are offering employees the flexibility to decide their work location on a daily basis (i.e., whether to work from home or to work in the office on a particular day). However, little is known about what factors drive employees' daily decisions to work from home versus office during the pandemic. Taking a social ecological perspective, we conceptualize employees' daily choice of work location (ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 67 publications
5
114
0
2
Order By: Relevance
“…Actually, in Reopening, HW, although possibly alternating with work at the office, was still a novelty or even a hazard for most employees and most organizations, thus, representing a relevant source of stress ( Hecker, 2020 ; Fukumura et al, 2021 ; Hamouche, 2021 ). Homeworkers not only have experienced an abrupt overlap between work and family lives ( Moretti et al, 2020 ) but also had to challenge a new working strategy, for which workers and organizations were largely unprepared ( Söderbacka et al, 2020 ; Shao et al, 2021 ; Xiao et al, 2021 ), so that most individuals were caught off guard and had to adjust by their means ( Guler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in Reopening, HW, although possibly alternating with work at the office, was still a novelty or even a hazard for most employees and most organizations, thus, representing a relevant source of stress ( Hecker, 2020 ; Fukumura et al, 2021 ; Hamouche, 2021 ). Homeworkers not only have experienced an abrupt overlap between work and family lives ( Moretti et al, 2020 ) but also had to challenge a new working strategy, for which workers and organizations were largely unprepared ( Söderbacka et al, 2020 ; Shao et al, 2021 ; Xiao et al, 2021 ), so that most individuals were caught off guard and had to adjust by their means ( Guler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such demands led to a decrease in employees' well‐being (e.g., Zacher & Rudolph, 2021 ). However, the pronounced demands in times of the COVID‐19 crisis, such as demands resulting from the blurriness of the work–family boundary (Shao et al, 2021 ), likely also pose constant challenges for employees' job performance (e.g., Gilboa et al, 2008 ). Corroborating this assumption, many employees reported to be less productive when working from home during the pandemic (e.g., Zacharakis & Loos, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…During an unprecedented public health crisis such as the COVID-19 pandemic, organizations must be able to both understand and address the challenges faced by their employees and stakeholders (e.g., McCarthy et al, 2021; Mo & Shi, 2020; Moen et al, 2020; Shao et al, 2021; Truxillo et al, 2020; Zhu et al, 2021). Our research identified employees’ death-related reactions as important pathways through which information exposure to a global health crisis may have implications for work behaviors.…”
Section: Discussionmentioning
confidence: 99%